Properties of Cement Brick Containing Expanded Polystyrene Beads (EPS) And Palm Oil Fuel Ash (POFA) - Kamarulzaman, N.A.; Adnan, S.H.; Mohd Sari, K.A.; Osman, M.H.; Ahmad Jeni, M.L.; Abdullah, M.S.; Ang Soon Ern, P.; Yahya, N.F.; Yassin, N.I.M; Wahee Anuar, M.N.A. (Journal of Science and Technology, 2018)
This paper assesses the mechanical properties of cement brick containing Expanded Polystyrene Beads (EPS) and Palm Oil Fuel Ash (POFA) as partial replacement of sand and Ordinary Portland Cement (OPC). The aim of this research are to determine the mechanical properties of brick containing EPS and POFA as partial replacement of sand and OPC. The dosage for EPS replacement is 20%, 30%, 40% and 50% EPS whereas 5%, 10%, 15%, 20% and 25% of POFA replacement. The mechanical properties of the bricks are density, compressive strength and water absorption. The bricks with 30%, 40% and 50% EPS replacement have density below 1680 kg/m3 which considered as lightweight brick. The brick with 50% EPS replacement recorded lowest density which is 1328 kg/m3 while 1629 kg/m3 for the brick withÂ  25% POFA replacement at 56-days of curing. The water absorption testing for these brick are between 7.20%-18.19%. Brick with 0% POFA and 50% EPS replacement has the lowest water absorption properties whereas brick with 25% POFA and 0% EPS replacement has the highest water absorption properties.